Photovoice and (Re)Socialisation of Offenders - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
Photovoice represents an innovative method of participatory action research based upon the theoretical concepts of visual and critical criminology and the scientific relevance of documentary photography. It allows specific social problems to be observed from the perspective of those who they affect most, with the aim to resolve these problems and initiate positive social changes. Photovoice is designed to provide the participants of the research with psychological support, empowerment, and personal development with the help of creative expression through photography. Photovoice enables the community and decision-makers to observe and understand the needs of the participants from the perspective of participants themselves – through their photographs and accompanying captions. Having in mind the expansion of the photovoice method in social studies and humanities, particularly for research and empowerment of marginalized groups, the author analyses the theoretical foundations of the photovoice method and the examples of its application in other countries for observation of offenders’ needs and enhancement of their resocialization. Within concluding remarks, the author discusses the advantages and limitations of the photovoice method and accentuates the need for its application in the research dedicated to resocialization and post-penal support of offenders in our country.